Trilhas ecológicas como recurso didático para a educação ambiental integrando educação física e biologia - Gaia, Paulino Pinheiro (2016)
The research aimed to develop interdisciplinary activities in ecological trails in Amazon NonFormal Spaces (ENFs), contributing to the formation of the individual in relation to environmental awareness. In this sense, to develop practices of this nature is considered as something of extreme importance for the contemporary world, allowing the knowledge of the world in its multiplicity, guaranteeing a more complete formation with prerogatives of efficient performance. The research problem arose because of the lack of initiative in relation to interdisciplinary activities that visualize regional natural resources (field classes) as a didactic alternative for the teaching of Environmental Education (EA). From this perspective, it is believed that the environment currently requires critical citizens, who can intervene in the improvements of society and the ecosystems in it. Thus, the research was developed with PARFOR students of the Second Degree in Biological Sciences of the Federal Institute of Education, Science and Technology of Amazonas (IFAM), Campus Manaus Centro (CMC), through interdisciplinary practices integrating the disciplines of Education (EF) and Biology (BIO), using as a teaching resource three ecological trails (ASFRAMA, Natal Waterfall and Urubuí Rapids) in the municipality of Presidente Figueiredo-AM. The proposal has the expected results the application of learning processes in an interdisciplinary way with contents developed by EF as corporal activities of adventure, nature recreation and hiking, integrating them with the biological knowledge that can be visualized in ecological trails. At the end of the research was created the website called "Ecological BIOEDPHYSICAL Tracks: Integrating Physical Education and Biology Education in EA" and the Board Game Didactic Ecological Trails in Presidente Figueiredo.